On the properties and atmospheric implication of amine-hydrated clusters. Issue 111 (26th October 2015) - Chen, Jiao; Jiang, Shuai; Miao, Shou-Kui; Peng, Xiu-Qiu; Ma, Yan; Wang, Chun-Yu; Zhang, Miao-Miao; Liu, Yi-Rong; Huang, Wei
Abstract : Amines have been recognized as important precursor species in the formation of new atmospheric particles. Abstract : Amines have been recognized as important precursor species in the formation of new atmospheric particles. Although dimethylamine–water clusters have been the focus of a large number of theoretical studies during the last few years, some information regarding these clusters, such as the influence of temperature, the analysis of their weak interactions, and their Rayleigh scattering properties, is still lacking. In this study, the equilibrium geometric structures and thermodynamics of (CH3 )2 NH(H2 O) n ( n = 1–6) clusters were systematically investigated using density functional theory (PW91PW91) coupled with the 6-311++G(3df, 3pd) basis set. To determine the most stable isomer and the order of the different isomers, single-point calculations were executed using a two-point extrapolation method in conjunction with the complete basis set for all isomers. The optimized structures show that the addition of a fifth water molecule changes the most stable configuration from a quasi-planar ring structure to a cage-like configuration. Electron density analysis shows that the interactions of these complexes are mainly medium hydrogen bonds. The dependence on temperature of the conformational population and the Gibbs free energies of the (CH3 )2 NH(H2 O) n ( n = 1–6) clusters were determined with respect to temperature (200–300 K). A weak dependence on temperature was found for the formation of (CH3 )2 NH(H2 O) n ( n = 1–6) clusters. Dimethylamine–water clusters are favorable at low temperatures, but these clusters may be difficult to form because of the combined effect of Gibbs free energies with small negative values and the low relative concentration of dimethylamine in various atmospheric conditions, and this implies that dimethylamine–water clusters are difficult to form spontaneously in the atmosphere. Finally, the Rayleigh scattering properties of (CH3 )2 NH(H2 O) n ( n = 1–6) have been investigated systematically for the first time.